Third-Degree Price Discrimination in Oligopoly when Markets are Covered - Markus Dertwinkel-Kalt; Christian Wey (The Journal of Industrial Economics, 2023)
We analyze oligopolistic third-degree price discrimination relative to uniform pricing when markets are covered. Pricing equilibria are critically determined by supply-side features such as the number of firms and their marginal cost differences. It follows that each firm's Lerner index under uniform pricing is equal to the weighted harmonic mean of the firm's relative margins under discriminatory pricing. Uniform pricing then lowers average prices and raises consumer surplus. We can calculate the gain in consumer surplus and loss in firms' profits from uniform pricing based only on the market data of the discriminatory equilibrium (i.e., prices and quantities).
Keywords: 330